2009
DOI: 10.1159/000257431
|View full text |Cite
|
Sign up to set email alerts
|

Catechins Inhibit CCL20 Production in IL-17A-Stimulated Human Gingival Fibroblasts

Abstract: CC chemokine ligand 20 (CCL20) plays a pivotal role in the recruitment of Th17 cells and thus in the development of periodontal disease. Epigallocatechin gallate (EGCG) and epicatechin gallate (ECG), the major catechins in green tea, have multiple beneficial effects, but the effects of catechins on CCL20 production in human gingival fibroblasts (HGFs) are not known. In this study, we investigated the mechanisms by which EGCG and ECG inhibit interleukin (IL)-17A-induced CCL20 production in human gingival fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…We observed that TNF-a-induced CCL20 production was dependent on STAT3, p38 and ERK. In line with this, IL-17-induced CCL20 was shown to be dependent on ERK activity in primary human tracheal cells [18], on both ERK and p38 activity in human gingival fibroblasts [19], and on phosphorylation of STAT3 in naïve T-lymphocytes [29]. ERK and p38 phosphorylation have previously been shown to be inhibited by glucocorticoids [30], while glucocorticoids induce IL-10 in a STAT3-dependent way in B-lymphocytes [31].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We observed that TNF-a-induced CCL20 production was dependent on STAT3, p38 and ERK. In line with this, IL-17-induced CCL20 was shown to be dependent on ERK activity in primary human tracheal cells [18], on both ERK and p38 activity in human gingival fibroblasts [19], and on phosphorylation of STAT3 in naïve T-lymphocytes [29]. ERK and p38 phosphorylation have previously been shown to be inhibited by glucocorticoids [30], while glucocorticoids induce IL-10 in a STAT3-dependent way in B-lymphocytes [31].…”
Section: Discussionsupporting
confidence: 61%
“…Since the STAT3, ERK and p38 pathways have been implicated in CCL20 transcription as well as in glucocorticoid-insensitive airway inflammation [18][19][20], we tested the effect of their specific inhibitors on the TNF-a-and budesonide-induced CCL20 production in 16HBE cells. Pre-incubation with the inhibitors of the ERK (U0126), p38 (SB203580) and STAT3 (S3I-201) pathways significantly reduced the TNF-a-induced CCL20 production, indicating a role for these signalling molecules in CCL20 production ( fig.…”
Section: Mechanisms Of Glucocorticoid-induced Ccl20 Secretion In 16hbmentioning
confidence: 99%
“…Inhibition of the IL-17R expression with siRNA in HGF cells showed that IL-17F may mediate the cytokine expression via ERK and NF-κB signaling pathways [33]. The chemokine CCL20 played a crucial role in the recruitment of Th17 cells and thus in the CP disease development [34]. While the IL-17A and IL-17F increased CCL20 production in HGF cells also indicated that CCL20 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-17 does not directly promote the chemotaxis of human neutrophils from peripheral blood [9]; rather, it promotes the release of recruitment factors from the inflamed microenvironment. Recent studies demonstrate that IL-17 induces the production of IL-6, IL-8, Gro-α, G-CSF, and CCL20 in epithelial cells, synovial fibroblasts, colonic myofibroblasts, and airway smooth muscle cells [10][11][12][13][14]. Moreover, the induction of these inflammatory factors promotes recruitment and accumulation of inflammatory cells, such as neutrophils [15].…”
Section: Introductionmentioning
confidence: 99%